Engineering cavity singlet fission in rubrene - Sun, Kewei (2022)
By employing the numerically exact multiple Davydov D2 ansatz, we study cavity-manipulated singlet fission that is mediated by polaritonic conical intersections for both one- and two-molecule systems. The population evolution of the TT state and the cavity photons is carefully examined in search for a high fission efficiency via cavity engineering. Several interesting mechanisms have been uncovered, such as photon-assisted singlet fission, system localization via a displaced photon state, and collective enhancement of the fission efficiency for the two-molecule system. It is also found that the system localization process in the two-molecule system differs substantially from that in the one-molecule system because of the appearance of a novel central polaritonic conical intersection in the two-molecule system. It has been demonstrated that the cavity-controlled singlet fission process can be switched on and off by controlling the average pumping photon number.